2018
DOI: 10.1158/1538-7445.am2018-98
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 98: Cell membrane cholesterol modulates lung cancer cell adhesion and rolling on E-selectin

Abstract: Despite numerous advances in cancer research, lung cancer has remained the major cause of cancer-related mortality worldwide, mainly because of metastasis and the lack of curative systemic therapy. It has been well established that lipid rafts, the membrane microdomains containing cholesterol and glycosphingolipids, play an important role in cell adhesion and spreading. Notably, there are elevated levels of cholesterol-rich lipid rafts observed in cancer cells relative to normal ones. Thus, alterations in lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One study found that raft disruption of TNBC cells via mβCD treatment significantly decreased cell adhesion on fibronectin and vitronectincoated substrates(20). Likewise, cholesterol depletion caused CD44 shedding from lipid rafts in cancer cells, suppressing adhesion, migration, and endothelial cell rolling(80,81). CD44 is known to interact with C1QBP in rafts to activate PI3K/MAPK downstream, a signaling pathway that also promotes cell adhesion and other pro-metastatic phenotypes(58).…”
mentioning
confidence: 99%
“…One study found that raft disruption of TNBC cells via mβCD treatment significantly decreased cell adhesion on fibronectin and vitronectincoated substrates(20). Likewise, cholesterol depletion caused CD44 shedding from lipid rafts in cancer cells, suppressing adhesion, migration, and endothelial cell rolling(80,81). CD44 is known to interact with C1QBP in rafts to activate PI3K/MAPK downstream, a signaling pathway that also promotes cell adhesion and other pro-metastatic phenotypes(58).…”
mentioning
confidence: 99%